Design and implementation of a state feedback controller for enhanced speed stability of permanent magnet DC motors under load variations - Mahdi Syukri; Rakhmad Syafutra Lubis; Melinda Melinda; Muhammad Hakkan Syukur; Iskandar Hasanuddin; Muhammad Irwanto (Politeknik Negeri Lhokseumawe, 2026)
This study presents the design and simulation of a State Feedback Controller (SFC) for speed regulation of a Permanent-Magnet DC (PMDC) motor using a state-space modeling approach. The objective is to achieve stable and accurate speed control under dynamic load disturbances that typically degrade the performance of conventional open-loop systems. The Direct Current (DC) motor is modeled in state-space form, with armature current and angular speed selected as the main system states. Controller gains are designed using the pole placement method to ensure fast response and improved stability. The proposed SFC is evaluated through MATLAB®/Simulink® simulations by examining motor speed, armature current, and input voltage responses under step-load variations. Simulation results show that the SFC maintains the motor speed at the reference value of 3,430 rpm even during sudden load increases, whereas the uncontrolled motor experiences significant speed drops and oscillations. Performance analysis confirms notable improvements in transient response. The rise time is reduced from 1.1864 s to 0.4220 s, and the settling time decreases from 2.1132 s to 0.7517 s, indicating faster and more stable system behavior. In addition, smoother current transitions and more efficient voltage regulation are achieved compared to the open-loop configuration. Overall, the results demonstrate that state-space control using pole placement provides a robust and responsive alternative to conventional PID controllers for DC motor speed control under load disturbances. Future work will focus on experimental validation and the exploration of advanced control strategies such as Linear Quadratic Regulation and adaptive control.